Correlation between working position of dentists and malondialdehyde concentration with musculoskeletal complaints - Hari Wibowo; Titiek Berniyanti; Jenny Sunariani (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: Musculoskeletal complainst of dentists have become common issues in dentistry since the awkward positions during treating the patients; such as position of a dentist who bends towards the patient, moving abruptly, twisting the body from a side to another side. All those movements are done several times in long term. Such high level of activity without sufficient recovery time may lead to an oxidative stress, so it will affect on the musculoskeletal and concentration of malondialdehyde (MDA) in blood. Purpose: To identify the correlation between malondialdehyde concentration on the risk of musculoskeletal complaint on dentist with working position of maxilla dental patching at community health center(Puskesmas) in Surabaya. Method: The type of research conducted was observational analytics using cross sectional approach. Sampling technique utilized in this research was cluster random sampling techniquewith the total samples of 19. Result: From data analysis result using Spearman correlation test, it was found that there was a significant correlation between working position and musculoskeletal complaint using Spearman correlation test and the p value obtained was<0.05. This research also found that there was a significant correlation between malondialdehyde concentration and musculoskeletal complaint using Pearson correlation test and the p value obtained was <0.05. Conclusion: There is a significant correlation between working positions of dentists and there is a significant correlation between working position and malondialdehydeconcentration with the musculoskeletal complaints.